Simplified Femoral Bone Model for Numerical Analysis of Proximal Femur - H. Khan, M.; Daud, R.; K. Ali Hassan, M.; F.Azizan, A. (International Journal of Engineering and Technology, 2018)
Numerous studies had been conducted to analyze the performance of implant for treating femoral head fractures utilizing finite element (FE) method. However, most studies use the whole femoral bone structure as the main model for conducting the numerical analysis. This will significantly increase the complexity to calculate the solution due to the higher number of meshing nodes and elements. Simplified femoral bone model without the shaft and distal region may be able to solve this issue. Thus, this study aimed to investigate the viability of simplified femoral bone model for conducting a numerical analysis of femoral head. In this study, two proximal bone models were constructed; by creating a cutting plane orthogonal to the shaft of the original model and another by cutting a plane orthogonal to the femoral head. The maximum stresses were measured along the femoral neck based from the simulated von Mises stresses. Based from the results, the proximal bone model with cut plane orthogonal to the femoral shaft showed the closes overall stress distribution to the original femoral bone model with 4.32% error. Thus, the simplified model is suitable to be used to replace the original femoral model for proximal femur FE analysis.Â Â